Disgorgement as Remedial Action in Indonesian Capital Market Regime - Uni Tsulasi Putri (Jurnal Hukum Novelty, 2020)
Introduction to The Problem: In 2019, Financial Services Authority introduced the disgorgement within the field of Indonesian Capital Market by the establishment of OJK Regulation Draft concerning Disgorgement and Disgorgement Fund in the Capital Market. Disgorgement itself is a very new concept in Indonesia. It is meant to be a remedial action, furthermore, it is expected to prevent Party for enjoyment of illegal profit, compensate the victim’s loss, containing corrective element, as well as to give deterrence effect.Purpose/Objective Study: This study aims to study on how the disgorgement as remedial action would apply and create deterrence effect in Indonesian Capital Market Regime.Design/Methodology/Approach: This is a normative legal research which uses qualitative research method. This study will conduct literature review and comparative study with disgorgement regulation within the field of securities law in common law and civil law jurisdiction.Findings: In upcoming disgorgement technical manner, OJK will give a written order for the Party who violate capital market regulation and pursuing illegally obtained profit or illegally avoided loss to return sum amount of money sum up with the interest (if any). To uphold this scheme, Indonesia needs to develop the theoretical framework such as actio de in rem verso or unjust enrichment. Furthermore, in order to create deterrence effect, Indonesia shall provide effective, proportionate and dissuasive sanction.